2007
DOI: 10.1097/01.mao.0000281803.36574.bc
|View full text |Cite
|
Sign up to set email alerts
|

Current Steering Creates Additional Pitch Percepts in Adult Cochlear Implant Recipients

Abstract: These results indicate that additional pitch percepts can be created using current steering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 9 publications
5
86
2
Order By: Relevance
“…Due to broad spread of currents through the scala tympani, it is possible to use electrodes separated by a distance of as much as 16 mm to evoke such intermediate pitches . The resolution, identified as the number of intermediate pitches, achievable with simultaneous stimulation has been quantified in several studies (Donaldson et al, 2005;Firszt et al, 2007;Koch et al, 2007). Generally, it is found that on average 4-7 intermediate pitch sensations per pair of adjacent electrodes (spaced between 0.85 and 1.1 mm, depending on electrode type) could be perceived using current steering, with a trend for basal pairs to produce fewer intermediate pitches.…”
Section: Evidence Of Current Steering In Human Subjectsmentioning
confidence: 99%
“…Due to broad spread of currents through the scala tympani, it is possible to use electrodes separated by a distance of as much as 16 mm to evoke such intermediate pitches . The resolution, identified as the number of intermediate pitches, achievable with simultaneous stimulation has been quantified in several studies (Donaldson et al, 2005;Firszt et al, 2007;Koch et al, 2007). Generally, it is found that on average 4-7 intermediate pitch sensations per pair of adjacent electrodes (spaced between 0.85 and 1.1 mm, depending on electrode type) could be perceived using current steering, with a trend for basal pairs to produce fewer intermediate pitches.…”
Section: Evidence Of Current Steering In Human Subjectsmentioning
confidence: 99%
“…This will affect or distort the intended perception and usually is undesirable. However, experiments show that by exciting two adjacent electrodes simultaneously in a suitable manner, 2,9,10,15,17,[22][23][24] the CI users can perceive a pitch which is between two pitches perceived when the two electrodes are excited individually. The intermediate pitch is the so called virtual channel since there is no real electrode to generate a real stimulation channel there.…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate pitch is the so called virtual channel since there is no real electrode to generate a real stimulation channel there. The mechanism for controlling the virtual channels, called current steering, 2,10,15,23 steers the current applied to adjacent electrodes in order to generate virtual channels according to the current ratio between the electrodes. This technique can be used to expand the spectral resolution without changing the implanted hardware or the number of CI electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations